Análise das congruências entre as perspectivas de valor para o cliente e da intenção organizacional em serviços educacionais - Nerva, Flávio da Cunha (Universidade do Vale do Rio do Sinos)
The acquisition of information on value for the customer becomes essential for the analysis of investments, current and futures in the products. The purpose of this work is to establish a structure of consistency analysis and possible trade-offs between what is value for the customer and for the organizational intention. The base of the proposal refers to the approach of the theory Chain end-means, which establishes a cognitive structure relating three levels that vary from concrete elements to the most abstract levels: attributes (How?), use consequences (What?) and values (Why?). The present study was elaborated using Laddering and in a quantitative phase for the Association Pattern Technique (APT), method for the construction of the Hierarchical Map of Value (HVM). The results presented evidence consistencies and inconsistencies in the three levels of the chain, in the two perspectives and between the two methods. The analysis of those results contributes to possible strategic decision-making in the m
Keywords: cliente; educação; gestão de serviços; técnica de associação de padrões; valor; administration of services; association pattern technique; customer value; education; laddering; Ciências Sociais Aplicadas